The book of Ezekiel chapters 1 - 24 - Block, Daniel Isaac, 1943- (Grand Rapids, MI Eerdmans, 1997)
Includes bibliographical references and indexes.
The reader should note that the introduction in this vol. is the introduction to the complete NICOT on Ezekiel (i.e.Vol 1 : Chapters 1 - 24 and Vol 2 : Chapters 25 - 48)
Keywords: Bible. O.T. Ezekiel I - XXIV -- commentaries